2019
DOI: 10.1111/dmcn.14333
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and sedentary behaviour in children with spina bifida

Abstract: Aim To describe active and sedentary time in children with spina bifida and to compare their physical activity on weekdays versus weekends. Method In this exploratory cross‐sectional study, data from 13 Canadian and 22 Dutch children with spina bifida (14 females, 21 males; mean age 10y 11mo, standard deviation [SD] 3y 6mo, range 5y 6mo–18y; Hoffer classification distribution: community [n=28], household [n=3], non‐functional [n=3], and non‐ambulator [n=1]) were analysed. Objective measures of physical activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 35 publications
0
14
0
1
Order By: Relevance
“…However, the aim of this intervention is to increase the active propulsion of the everyday wheelchair and the Activ8 is a valid device for detecting this component of PA [27]. Only data of participants with a minimal wear time of eight hours/day on at least two school-days and one weekend-day were analysed [6]. The main outcome for PA is the amount of "active wheelchair use" expressed as a percentage of wear time per day.…”
Section: Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the aim of this intervention is to increase the active propulsion of the everyday wheelchair and the Activ8 is a valid device for detecting this component of PA [27]. Only data of participants with a minimal wear time of eight hours/day on at least two school-days and one weekend-day were analysed [6]. The main outcome for PA is the amount of "active wheelchair use" expressed as a percentage of wear time per day.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…It has been shown that low levels of physical activity (PA) are more prevalent among youth (children and adolescents) with a physical disability compared to their typically developing peers [3,4]. Youth using a manual wheelchair are markedly less physically active than their ambulatory peers with or without a physical disability [5][6][7][8]. Bloemen et al [5] found that youth using a manual wheelchair with spina bifida were 2.5 times less physically active than typically developing peers.…”
Section: Introductionmentioning
confidence: 99%
“…They often suffer from abdominal obesity, insulin resistance or dyslipidemia with its metabolic and vascular complications [51]. People with physical disabilities spend less time performing physical activities compared to their nondisabled peers [52]. Consequences of a sedentary lifestyle include physical deconditioning [53].…”
Section: Cardiometabolic Dysfunctionmentioning
confidence: 99%
“…There is a potential for physical therapeutist to cooperate with local sport clubs and fitness centres to develop activity programs and supervise them [51]. Physical activities offer possibility to prevent other problems, such as obesity, metabolic problems or depression [52].…”
Section: Rehabilitation Medicine and Physical Therapymentioning
confidence: 99%
“…A study's participants being aged above 20 years was an exclusion criterion. The authors state that it is worth doing research on a population of a similar age without a lot of discrepancies (Bloemen et al, 2017;Kalleson et al, 2019;Lauruschkus et al, 2015;Romero, 2019;Claridge et al, 2019;Howells et al 2019;Cook et al, 2015;Spencer-Cavaliere & Watkinson, 2010). A child physical and mental development is very intensive and really diverse when we take various developmental stages into consideration.…”
Section: Exclusion Criteriamentioning
confidence: 99%